Early Management of Pseudo-Class III Malocclusion in a Growing Child with a Reverse Twin Block Appliance: A Case Report - Rifki, Ayudia; Yulina, Vera; Ulfah, Khairiyah; Rambe, Sarinah; Fitri, Maida (Journal of Syiah Kuala Dentistry Society, 2025)
Background: Pseudo Class III malocclusion is characterized by an anterior crossbite with functional forward mandibular displacement. This malocclusion can prevent maxillary sagittal development, and if not intervened upon promptly, can develop into a skeletal class III malocclusion. Therefore, it is essential to avoid this malocclusion as early as possible. Case Report: A 9-year-old male child presented with the chief complaint of prominent lower teeth. Intra-oral examination showed crossbite anterior, presence of crowding, and malposition 21,22. Right molar relation class 1 and left class III, maxillary space discrepancy 6.4 mm, skeletal Class I, patient in growth and development period. Treatment was performed using a functional appliance, a reverse twin block, with additional bilateral expansion on the maxilla and a Z-spring on teeth 21 and 22. Conclusion: Management of pseudo-class III in growing children with reverse twin block has shown success in correcting the crossbite anterior, tooth malposition, and increasing the maxillary arch width.